(untitled) (Isagoge - Journal of Humanities and Social Sciences, 2021)
Non-completion among university students is a common phenomenon in many parts of the world. Many causes of this problem have been advanced and among them are institutional and individual reasons like financial ability, gender and motivation to complete studies. Psychological distress though not investigated thoroughly has been cited as one of the problems leading to non-completion. The purpose of this study was to establish the relationship between psychological distress and non-completion among postgraduate students in selected public universities in Kenya. Weiner Attribution theory (1985) informed the study. The study adopted a correlation research design and it was conducted in two selected public universities in Uasin Gishu and Nairobi counties targeting a population of 945 postgraduate students. A sample of (N=273) was obtained from the two selected public universities through systematic random sampling. The study used questionnaires, focus group discussions and document analysis in collecting data. Reliability of the questionnaire was established using Split half method from a pilot study conducted in Uasin Gishu County. Statistical package for the social sciences SPSS 23 was also used to analyze the data .Descriptive statistics to analyze demographic data while Pearson correlation was employed to test the relationship between psychological distress and non-completion. Regression analysis was used to clarify the nature of relationship with the variable. Findings indicated a weak negative correlation between psychological distress and non-completion, not statistically significant, rs (229) =-.063, p ˃ .05. However, descriptive findings established that a majority of students 34.1% agreed that psychological distress could lead to non-completion. It recommended that students plan for their study schedules and finances to ensure study period is not interrupted by roles that can be put on hold like parenting and inadequate finances. Further the university administration should put in place / reinforce committees that handle non-completion among students. Development and implementation of postgraduate policy that would track postgraduate journey, as well as establishment of course advisory, guidance and counselling for this students.